2008
DOI: 10.1002/sia.2907
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization‐induced optical second harmonic generation from the surface of Co‐doped rutile TiO2(110)

Abstract: We have investigated the surface magnetism of 5 at% Co-doped rutile TiO 2 (110) using magnetization-induced optical second harmonic generation (MSHG) in the longitudinal Kerr configuration with the incident beam angle of 4• . MSHG is observed at both 2 ω = 2.33 eV and 2 ω = 4.20 eV. MSH intensity showed a hysteresis as a function of the external magnetic field for the second harmonic photon energy of 2 ω = 4.20 eV at which the absorption length limits the MSHG origin to the surface layer of 10 nm due to the Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…We have found that the surface magnetization showed an anisotropic two-lobed pattern and suggest that this two-lobed pattern reflects the anisotropy of the magnetization of the surface Co ions due to the ligand field of oxygen. Hence the judgment made in our previous paper [9], that 5 at% Co:rutile TiO 2 (1 1 0) is a ferromagnetic dilute magnetic semiconductor at its surface, has been reconfirmed in this study.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…We have found that the surface magnetization showed an anisotropic two-lobed pattern and suggest that this two-lobed pattern reflects the anisotropy of the magnetization of the surface Co ions due to the ligand field of oxygen. Hence the judgment made in our previous paper [9], that 5 at% Co:rutile TiO 2 (1 1 0) is a ferromagnetic dilute magnetic semiconductor at its surface, has been reconfirmed in this study.…”
Section: Discussionsupporting
confidence: 56%
“…2 demonstrate superparamagnetic behavior. In our previous paper [9] we reported that with a different SH photon energy, this sample showed hysteresis in SH intensity as a function of the applied magnetic field. Therefore, the surface of this sample is ferromagnetic.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations